An aluminum alloy for an ultra-high-strength high-toughness 7-series crash beam and a method of manufacturing the same

CN122918399APending Publication Date: 2026-10-16广东豪美技术创新研究院有限公司 +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611048453.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

6系铝合金具有良好的挤压成型性和耐腐蚀性,但其屈服强度通常在240~300 MPa范围内,难以满足更高的防护需求

Benefits of technology

1.本发明通过优化铝合金的成分,并加入Al-Sr-Re稀土变质处理、两级均匀化、在线淬火以及双级时效工艺的协同作用,最终制备的铝合金防撞梁抗拉强度≥580 MPa,屈服强度≥550 MPa,延伸率≥13%。相比现有技术中高强7系铝合金普遍存在的高强度低塑性问题(延伸率通常≤10%甚至更低),本发明在保证屈服强度超过550 MPa的同时,将延伸率提升至13%以上,实现高强度与高韧性的优异匹配,能够充分满足汽车防撞梁在碰撞过程中吸能防撞的安全需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122918399A_ABST
    Figure CN122918399A_ABST
Patent Text Reader

Abstract

The application discloses an aluminum alloy for a super-high-strength and high-toughness 7-series anti-collision beam and a preparation method thereof, and belongs to the technical field of aluminum alloy preparation. Through the synergistic effect of optimization of components, Al-Sr-Re modification, two-stage homogenization, online quenching and double-stage aging, the aluminum alloy has a tensile strength of greater than or equal to 580 MPa, a yield strength of greater than or equal to 550 MPa and an elongation of greater than or equal to 13%, overcomes the defects of high strength and low plasticity (elongation less than or equal to 10%) of the existing 7-series aluminum alloy, and realizes excellent matching of strength and toughness. After online solid solution, low-temperature pre-aging is introduced to form a stable GP zone to inhibit natural aging and lock the mechanical state in a suitable plastic interval of tensile bending, thereby reducing the cracking risk and improving the yield. The two-stage homogenization effectively eliminates dendritic segregation; the double-stage aging causes a large number of fine GP zones and eta prime phases to be formed in the crystal to ensure the strength, causes discontinuous eta phases to be formed at the grain boundaries and narrows the unprecipitated zone, and improves the intergranular fracture resistance, thereby comprehensively improving the plasticity and toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of aluminum alloy technology, and more specifically, to an aluminum alloy for ultra-high strength and high toughness 7-series anti-collision beams and its preparation method. Background Technology

[0002] As a core structural component of a car's frontal collision protection system, the crash beam plays a crucial role in absorbing collision energy and protecting the passenger compartment. Traditionally, automotive crash beams are mainly made of hot-formed steel or high-strength steel. While the strength is sufficient, the high density results in high weight, hindering the achievement of overall vehicle lightweighting goals. With the development of aluminum alloy processing technology, 6-series aluminum alloys (Al-Mg-Si series) have been applied to crash beams in some mid-to-high-end models. 6-series aluminum alloys have good extrusion formability and corrosion resistance, but their yield strength is typically in the range of 240-300 MPa, making it difficult to meet higher protection requirements. Research indicates that 7-series aluminum alloys can be used in automotive crash beam components with high strength requirements, achieving a weight reduction of over 20% compared to 6-series aluminum alloys.

[0003] 7-series aluminum alloys (Al-Zn-Mg-Cu series) are a class of heat-treatable, ultra-high-strength aluminum alloys. Through rational composition design and heat treatment process control, 7-series aluminum alloys can achieve mechanical properties far exceeding those of 6-series aluminum alloys while maintaining lower density. Studies have shown that, for the same cross-section, the strength of 7-series aluminum alloys is approximately 1.5 to 2 times higher than that of 6-series alloys. Under the same strength requirements, wall thickness can be reduced and cross-sections smaller, achieving a 15% to 30% weight reduction effect for a single anti-collision beam. Replacing steel anti-collision beams can achieve a weight reduction of over 60%. Although 7-series aluminum alloys have significant advantages in the field of automotive lightweighting, their large-scale engineering application still faces a series of technical bottlenecks, mainly in the following aspects: First, 7-series aluminum alloys are ultra-high-strength aluminum alloys with a narrow working window. During extrusion molding, the alloy has poor fluidity, making it prone to surface cracks and internal defects. Bending is a critical process in the manufacture of high-strength crash beams; limited by the material's high strength and low plasticity, cracking easily occurs during bending, requiring extremely high precision in mold design and forming parameter control. Second, 7-series aluminum alloys require strict solution quenching and aging treatments to achieve the designed strength. Their heat treatment temperature range is narrow; excessively high solution treatment temperatures can lead to overheating, while excessively low temperatures result in insufficient solution treatment. Quenching processes are prone to defects such as quenching deformation and dimensional warping. This is especially true for slender, thin-walled crash beam profiles, where post-heat treatment reshaping is extremely difficult, making yield control challenging. Third, 7-series aluminum alloys exhibit a strong natural aging effect after solution quenching. During storage, solute atoms rapidly aggregate into clusters, undergoing natural aging strengthening, leading to a gradual increase in strength and a decrease in plasticity, thus affecting subsequent bending molding and even causing bending cracks. This problem is more pronounced under the high temperatures of summer in the south. Therefore, existing processes typically require bending to be completed within a very short time after extrusion molding, which poses a significant challenge to actual production organization.

[0004] In the prior art, patents related to 7-series aluminum alloy anti-collision beams are disclosed. For example, Chinese patent application number CN202211168686.6 discloses a high-strength, high-bending-performance 7-series anti-collision beam for automobiles. After T6 aging, the final product performance (7003-T6) can reach Rp0.2≥350MPa, Rm≥390MPa, and A50≥12. Another example is Chinese patent application number CN202510207768.4, which discloses a high-strength aluminum alloy extruded profile for automotive anti-collision beams and its preparation method. This invention, through optimized component ratios and a two-stage aging process, achieves a tensile strength of 370-410MPa, a yield strength of 320-370MPa, an elongation at break (A50) ≥11%, and a three-point bending energy absorption ≥4.50KJ, meeting the energy absorption requirements of high-speed collisions. However, most existing solutions focus primarily on further improving the strength limit of 7-series aluminum alloys, neglecting the overall balance between high strength and toughness. During a collision, the anti-collision beam needs to absorb a large amount of energy, requiring both sufficient plastic deformation capacity and tensile strength. Excessive strength coupled with insufficient plasticity can lead to brittle fracture, failing to fully realize its energy-absorbing function.

[0005] Therefore, there is still a lack of a 7-series aluminum alloy anti-collision beam material and its preparation method that combines ultra-high strength (yield strength > 550 MPa) and good plasticity (elongation > 13%) to meet the growing dual needs of lightweighting and safety protection for new energy vehicles. Summary of the Invention

[0006] Based on this, in order to solve one of the above-mentioned technical problems, the present invention provides an aluminum alloy for ultra-high strength and high toughness 7-series anti-collision beams and its preparation method, the specific technical solution of which is as follows: A method for preparing an aluminum alloy for ultra-high strength and high toughness 7-series anti-collision beams, the method comprising the following steps: S1. Add aluminum alloy raw materials to a melting furnace for melting to obtain molten aluminum; S2. Add Al-Sr-Re rare earth modifier to the aluminum liquid, and then cast the modified aluminum liquid in a vacuum direct cooling casting system. The casting process adopts vacuum online degassing to obtain aluminum alloy casting rods. S3. The aluminum alloy casting rod is subjected to a two-stage homogenization treatment. The first stage is held at 430~450℃ for 4~6 h, and the second stage is held at 470~490℃ for 23~25 h. After treatment, it is cooled to room temperature by water. S4. Heat the homogenized casting rod to 470~500℃, with a temperature gradient of 10~30℃ between the head and tail of the casting rod; heat the extrusion die to 470~490℃ and the die cylinder to 400~410℃. S5. The preheated casting rod is extruded, and a traction machine is used to synchronously pull the material during the discharge process to obtain the extruded product. S6. The extruded product is subjected to online solution treatment, and the online solution treatment adopts an online water cooling method; S7. The product that has completed online solution treatment is subjected to straightening and cutting sawing, low temperature pre-aging treatment, bending treatment and two-stage aging treatment to obtain aluminum alloy for ultra-high strength and high toughness 7-series anti-collision beams.

[0007] Furthermore, the aluminum alloy raw material comprises the following chemical composition by mass percentage: Zn: 6.8~8.5%, Mg: 1.9~2.7%, Cu: 0.8~1.6%, Ti+Zr≤0.25%, Si<0.4%, Fe≤0.5%, Mn≤0.5%, Cr≤0.3%, with the balance being aluminum and unavoidable impurities.

[0008] Furthermore, in step S2, the casting speed is 70~80 mm / min, the flow rate of argon gas used for online degassing is 60~90 nl / min, and the rotor speed of the degassing box is 700 RPM.

[0009] Further, in step S2, in the Al-Sr-Re rare earth modifier, Re is selected from one or more of La, Ce, Pr, and Nd, and the mass ratio of Sr to Re is (5~10):(8~12); the amount of Al-Sr-Re rare earth modifier added is 2.0~3.0Kg / T aluminum liquid.

[0010] Furthermore, in step S5, the extrusion ratio of the extrusion process is 25, and the extrusion discharge speed is 2~3m / min.

[0011] Furthermore, in step S6, the conductivity of the circulating water in the online water-cooling method is ≤300 μS / cm. 3 Water temperature ≤38℃, water pressure 0.4~0.5MPa.

[0012] Furthermore, in step S7, the straightening rate is 0.8~1.2%.

[0013] Furthermore, in step S7, the temperature of the low-temperature pre-aging treatment is 60~80℃, and the time is 1~3h.

[0014] Furthermore, in step S7, the two-stage aging treatment is as follows: the first stage of aging is carried out at 80~100℃ for 4~6 hours, and the second stage of aging is carried out at 120~140℃ for 12~16 hours.

[0015] In addition, the present invention also provides an aluminum alloy for ultra-high strength and high toughness 7-series anti-collision beams, wherein the aluminum alloy for ultra-high strength and high toughness 7-series anti-collision beams is prepared by the preparation method described above.

[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention optimizes the composition of aluminum alloys and incorporates the synergistic effects of Al-Sr-Re rare earth modification treatment, two-stage homogenization, online quenching, and two-stage aging processes. The resulting aluminum alloy crash beam exhibits a tensile strength ≥580 MPa, a yield strength ≥550 MPa, and an elongation ≥13%. Compared to the common problem of high strength and low plasticity (elongation typically ≤10% or even lower) in existing high-strength 7-series aluminum alloys, this invention achieves an excellent balance between high strength and high toughness while maintaining a yield strength exceeding 550 MPa. This fully meets the safety requirements of automotive crash beams for energy absorption and collision protection during impacts.

[0017] 2. This invention introduces a low-temperature pre-aging treatment after online solution treatment and before bending treatment, allowing solute atoms in the alloy to form stable GP zones in advance, effectively suppressing the tendency of 7-series aluminum alloys to undergo rapid natural aging at room temperature. After the low-temperature pre-aging treatment, the mechanical state of the alloy is locked within the plastic range suitable for bending forming, which helps to reduce bending cracks and improve the yield of products.

[0018] 3. This invention employs a two-stage homogenization process, effectively eliminating dendritic segregation and achieving excellent homogenization. This effectively avoids microstructural defects caused by compositional inhomogeneity during subsequent extrusion. Furthermore, a two-stage aging process is used. The first stage of aging forms numerous fine GP regions and η′ phases within the grains, contributing significantly to strength. The second stage of aging causes the η′ phase to grow slightly and maintain a high number density, while simultaneously forming discontinuous fine η phases at grain boundaries, significantly narrowing the width of the grain boundary precipitate-free zone and reducing atomic diffusion channels at grain boundaries. This microstructure, synergistically regulated by the grains and grain boundaries, ensures the strength of the aluminum alloy and improves its resistance to intergranular fracture, thereby enhancing the overall plasticity and toughness of the aluminum alloy. Attached Figure Description

[0019] The invention will be further understood from the following description taken in conjunction with the accompanying drawings. The components in the drawings are not necessarily drawn to scale, but rather the emphasis is on illustrating the principles of the embodiments. In different views, the same reference numerals designate corresponding parts.

[0020] Figure 1 This is a homogeneous SEM image of the aluminum alloy casting rod of Embodiment 1 of the present invention; Figure 2 This is a homogeneous SEM image of the aluminum alloy casting rod of Embodiment 2 of the present invention; Figure 3 This is a homogeneous SEM image of the aluminum alloy casting rod of Embodiment 3 of the present invention; Figure 4 This is a schematic diagram of the grain structure of the aluminum alloy formed in Embodiment 1 of the present invention; Figure 5 This is a schematic diagram of the grain structure of the aluminum alloy formed in Embodiment 2 of the present invention; Figure 6 This is a schematic diagram of the grain structure of the aluminum alloy formed in Embodiment 3 of the present invention. Detailed Implementation

[0021] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to its embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and do not limit the scope of protection of the invention.

[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0023] A method for preparing an aluminum alloy for an ultra-high strength and high toughness 7-series anti-collision beam according to one embodiment of the present invention, the method comprising the following steps: S1. Add aluminum alloy raw materials to a melting furnace for melting to obtain molten aluminum; S2. Add Al-Sr-Re rare earth modifier to the aluminum liquid, and then cast the modified aluminum liquid in a vacuum direct cooling casting system. The casting process adopts vacuum online degassing to obtain aluminum alloy casting rods. S3. The aluminum alloy casting rod is subjected to a two-stage homogenization treatment. The first stage is held at 430~450℃ for 4~6 h, and the second stage is held at 470~490℃ for 23~25 h. After treatment, it is cooled to room temperature by water. S4. Heat the homogenized casting rod to 470~500℃, with a temperature gradient of 10~30℃ between the head and tail of the casting rod; heat the extrusion die to 470~490℃ and the die cylinder to 400~410℃. S5. The preheated casting rod is extruded, and a traction machine is used to synchronously pull the material during the discharge process to obtain the extruded product. S6. The extruded product is subjected to online solution treatment, and the online solution treatment adopts an online water cooling method; S7. The product that has completed online solution treatment is subjected to straightening and cutting sawing, low temperature pre-aging treatment, bending treatment and two-stage aging treatment to obtain aluminum alloy for ultra-high strength and high toughness 7-series anti-collision beams.

[0024] In one embodiment, the aluminum alloy raw material comprises the following chemical composition by mass percentage: Zn: 6.8~8.5%, Mg: 1.9~2.7%, Cu: 0.8~1.6%, Ti+Zr≤0.25%, Si<0.4%, Fe≤0.5%, Mn≤0.5%, Cr≤0.3%, with the balance being aluminum and unavoidable impurities.

[0025] In one embodiment, in step S2, the casting speed is 70~80 mm / min, the flow rate of argon gas used for online degassing is 60~90 nl / min, and the rotor speed of the degassing box is 700 RPM.

[0026] In one embodiment, in step S2, the Re in the Al-Sr-Re rare earth modifier is selected from one or more of La, Ce, Pr, and Nd, and the mass ratio of Sr to Re is (5~10):(8~12); the amount of Al-Sr-Re rare earth modifier added is 2.0~3.0 kg / T of aluminum liquid. In the Al-Sr-Re rare earth modifier used in this invention, the mass ratio of Sr to Re is (5~10):(8~12). This modifier plays multiple roles in the melt: Re forms a high-melting-point Al-Re intermetallic compound with Al, serving as a heterogeneous nucleation core and significantly refining the as-cast grains; Sr changes the oxide film morphology, reducing the hydrogen content and inclusions in the ingot, and improving the purity of the melt; the synergistic effect of Sr-Re pins grain boundaries during subsequent homogenization and extrusion processes, inhibiting abnormal growth of recrystallized grains, ultimately obtaining a fine, uniform, and equiaxed grain structure. These effects collectively improve the alloy's processability and reduce the risk of cracking during extrusion and bending.

[0027] In one embodiment, in step S5, the extrusion ratio of the extrusion process is 25, and the extrusion discharge speed is 2~3m / min.

[0028] In one embodiment, in step S6, the conductivity of the circulating water in the online water-cooling method is ≤300 μS / cm. 3 Water temperature ≤38℃, water pressure 0.4~0.5MPa.

[0029] In one embodiment, in step S7, the straightening rate is 0.8~1.2%.

[0030] In one embodiment, in step S7, the temperature of the low-temperature pre-aging treatment is 60~80℃ and the time is 1~3h.

[0031] In one embodiment, in step S7, the two-stage aging process is as follows: the first stage of aging is performed at 80~100℃ for 4~6 hours, and the second stage of aging is performed at 120~140℃ for 12~16 hours.

[0032] In addition, the present invention also provides an aluminum alloy for ultra-high strength and high toughness 7-series anti-collision beams, wherein the aluminum alloy for ultra-high strength and high toughness 7-series anti-collision beams is prepared by the preparation method described above.

[0033] The implementation schemes of the present invention will now be described in detail with reference to specific embodiments.

[0034] Example 1: A method for preparing an aluminum alloy for an ultra-high strength and high toughness 7-series anti-collision beam includes the following steps: S1. Add aluminum alloy raw materials to a melting furnace for melting to obtain molten aluminum; The aluminum alloy raw material comprises the following chemical composition by mass percentage: Zn: 7.5%, Mg: 2.3%, Cu: 1.2%, Ti: 0.1%, Zr: 0.1%, Si: 0.25%, Fe: 0.3%, Mn: 0.15%, Cr: 0.1%, with the balance being aluminum and unavoidable impurities; S2. Add Al-7Sr-10La master alloy (Sr to La mass ratio of 7:10) to the aluminum liquid at an addition rate of 2.5Kg / T. Then, cast the modified aluminum liquid in a vacuum direct cooling casting system at a casting speed of 75mm / min. The casting process adopts vacuum online degassing with an argon flow rate of 75nl / min and a degassing box rotor speed of 700RPM to obtain aluminum alloy casting rods. S3. The aluminum alloy casting rod is subjected to a two-stage homogenization treatment. The first stage is held at 440℃ for 5 hours, and the second stage is held at 480℃ for 24 hours. After treatment, it is cooled to room temperature by water. S4. Heat the homogenized casting rod to 485℃, with a temperature gradient of 10℃ between the head and tail of the casting rod; heat the extrusion die to 480℃ and the die cylinder to 405℃; S5. The preheated casting rod is extruded, and a traction machine is used to synchronously pull the material during the discharge process to obtain the extruded product. S6. The extruded product is subjected to online solution treatment, and the online solution treatment adopts an online water cooling method, wherein the conductivity of the circulating water is ≤300 μS / cm. 3 The water temperature is 30℃ and the water pressure is 0.45MPa. S7. The product that has completed the online solution treatment is straightened and sawn with a straightening rate of 1%. Then it is subjected to low-temperature pre-aging treatment at 70℃ for 2 hours, bending treatment, and two-stage aging treatment. The two-stage aging treatment is as follows: the first stage of aging is held at 90℃ for 5 hours, and the second stage of aging is held at 130℃ for 14 hours to obtain the aluminum alloy for ultra-high strength and high toughness 7-series anti-collision beams.

[0035] Example 2: A method for preparing an aluminum alloy for an ultra-high strength and high toughness 7-series anti-collision beam includes the following steps: S1. Add aluminum alloy raw materials to a melting furnace for melting to obtain molten aluminum; The aluminum alloy raw material comprises the following chemical composition by mass percentage: Zn: 7.2%, Mg: 2.0%, Cu: 0.9%, Ti: 0.1%, Zr: 0.1%, Si: 0.2%, Fe: 0.3%, Mn: 0.15%, Cr: 0.1%, with the balance being aluminum and unavoidable impurities; S2. Add Al-7Sr-9Ce master alloy (Sr to Ce mass ratio of 7:9) to the aluminum liquid at an addition rate of 2.5Kg / T. Then, cast the modified aluminum liquid in a vacuum direct cooling casting system at a casting speed of 75mm / min. The casting process adopts vacuum online degassing with an argon flow rate of 75nl / min and a degassing box rotor speed of 700RPM to obtain aluminum alloy casting rods. S3. The aluminum alloy casting rod is subjected to a two-stage homogenization treatment. The first stage is held at 440℃ for 5 hours, and the second stage is held at 490℃ for 24 hours. After treatment, it is cooled to room temperature by water. S4. Heat the homogenized casting rod to 495℃, with a temperature gradient of 10℃ between the head and tail of the casting rod; heat the extrusion die to 490℃ and the die cylinder to 410℃. S5. The preheated casting rod is extruded, and a traction machine is used to synchronously pull the material during the discharge process to obtain the extruded product. S6. The extruded product is subjected to online solution treatment, and the online solution treatment adopts an online water cooling method, wherein the conductivity of the circulating water is ≤300 μS / cm. 3 The water temperature is 30℃ and the water pressure is 0.45MPa. S7. The product that has completed the online solution treatment is straightened and sawn with a straightening rate of 1%, then pre-aged at 80℃ for 1 hour, followed by bending treatment and two-stage aging treatment. The two-stage aging treatment is as follows: the first stage of aging is held at 100℃ for 4 hours, and the second stage of aging is held at 140℃ for 12 hours, to obtain the aluminum alloy for ultra-high strength and high toughness 7-series anti-collision beams.

[0036] Example 3: A method for preparing an aluminum alloy for an ultra-high strength and high toughness 7-series anti-collision beam includes the following steps: S1. Add aluminum alloy raw materials to a melting furnace for melting to obtain molten aluminum; The aluminum alloy raw material comprises the following chemical composition by mass percentage: Zn: 7.5%, Mg: 2.2%, Cu: 1.1%, Ti: 0.1%, Zr: 0.12%, Si: 0.25%, Fe: 0.3%, Mn: 0.15%, Cr: 0.1%, with the balance being aluminum and unavoidable impurities; S2. Add Al-9Sr-12Pr master alloy (Sr to Pr mass ratio of 9:12) to the aluminum liquid at an addition rate of 2.5Kg / T. Then, cast the modified aluminum liquid in a vacuum direct cooling casting system at a casting speed of 75mm / min. The casting process adopts vacuum online degassing with an argon flow rate of 75nl / min and a degassing box rotor speed of 700RPM to obtain aluminum alloy casting rods. S3. The aluminum alloy casting rod is subjected to a two-stage homogenization treatment. The first stage is held at 435℃ for 6 hours, and the second stage is held at 475℃ for 25 hours. After treatment, it is cooled to room temperature by water. S4. Heat the homogenized casting rod to 475℃, with a temperature gradient of 10℃ between the head and tail of the casting rod; heat the extrusion die to 470℃ and the die cylinder to 400℃. S5. The preheated casting rod is extruded, and a traction machine is used to synchronously pull the material during the discharge process to obtain the extruded product. S6. The extruded product is subjected to online solution treatment, and the online solution treatment adopts an online water cooling method, wherein the conductivity of the circulating water is ≤300 μS / cm. 3 The water temperature is 30℃ and the water pressure is 0.45MPa. S7. The product that has completed the online solution treatment is straightened and sawn with a straightening rate of 1%, then pre-aged at 60℃ for 3 hours, followed by bending treatment and two-stage aging treatment. The two-stage aging treatment is as follows: the first stage of aging is held at 100℃ for 4 hours, and the second stage of aging is held at 140℃ for 12 hours, to obtain the aluminum alloy for ultra-high strength and high toughness 7-series anti-collision beams.

[0037] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that Al-7Sr-10La master alloy was not added in Comparative Example 1, but otherwise it is the same as Example 1.

[0038] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that the homogenization treatment in Comparative Example 2 was carried out at a temperature of 480°C for 24 hours, while the rest was the same as in Example 1.

[0039] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that the aging treatment in Comparative Example 3 was carried out at 120°C for 24 hours, while the rest was the same as in Example 1.

[0040] Comparative Example 4: The difference between Comparative Example 4 and Example 1 is that Comparative Example 4 did not undergo a low-temperature pre-aging treatment at 70°C for 2 hours; otherwise, it was the same as Example 1.

[0041] Comparative Example 5: The difference between Comparative Example 5 and Example 1 is that the mass percentage content of the aluminum alloy raw materials in Comparative Example 5 is different, while the rest is the same as in Example 1. The aluminum alloy raw material in Comparative Example 5 contains the following chemical composition by mass percentage: Zn: 5.8%, Mg: 1.2%, Cu: 0.5%, Ti: 25%, Zr: 0.15%, Si: 0.25%, Fe: 0.3%, Mn: 0.15%, Cr: 0.1%, with the balance being aluminum and unavoidable impurities.

[0042] Comparative Example 6: The difference between Comparative Example 6 and Example 1 is that Comparative Example 6 uses an Al-7Sr-1La master alloy (i.e., the mass ratio of Sr to La is 7:1), while the rest is the same as Example 1.

[0043] The aluminum alloy samples prepared in Examples 1-3 and the aluminum alloy samples prepared in Comparative Examples 1-6 were subjected to performance tests, and the results are shown in Table 1 below.

[0044] Table 1: Performance Test Results

[0045] Analysis of the data in Table 1 shows that, after optimization of composition and process, the tensile strength of Examples 1-3 is ≥589 MPa, yield strength ≥563 MPa, elongation ≥14.2%, and the as-cast grain size is small, resulting in a high yield rate in tensile bending. This indicates that the present invention, through the synergistic effects of alloy composition optimization, Al-Sr-Re modification treatment, two-stage homogenization, low-temperature pre-aging, and two-stage aging, successfully achieved an excellent match between high strength and high plasticity (yield >550 MPa, elongation >14%), while also exhibiting good processability. Compared with Example 1, Comparative Example 1 did not add Al-7Sr-1La master alloy, and the grain coarsening led to a decrease in strength and plasticity. This indicates that the addition of Al-Sr-Re modifier significantly refines the as-cast grains by forming heterogeneous nucleation cores of Al-Re intermetallic compounds; at the same time, Sr element purifies the melt and reduces defects, and Sr-Re synergistically pins grain boundaries to inhibit recrystallization coarsening. Comparative Example 2, with its different homogenization process, failed to fully eliminate dendrite segregation, leading to uneven distribution of precipitated phases during subsequent aging. This resulted in significant deterioration of both strength and plasticity. This demonstrates that the two-stage homogenization process of this invention allows the low-melting-point eutectic phase to dissolve slowly, preventing overheating, while the high-temperature stage promotes sufficient solute diffusion, contributing to improved aluminum alloy performance. Comparative Example 3, with its different aging process, achieved higher strength, but its plasticity was significantly worse than Example 1. This indicates that under single-stage aging, the grain boundary precipitates exhibit a continuous chain distribution, making them prone to cracking during deformation. For automotive anti-collision beams, absorbing a large amount of energy during collisions is crucial; excessively high strength combined with extremely low plasticity can lead to brittle fracture, reducing energy absorption safety. Comparative Example 4, without a 2-hour low-temperature pre-aging treatment at 70°C, experienced rapid natural aging during room temperature storage, resulting in decreased plasticity and a significant increase in cracking rate during bending. In contrast, Example 1, after a 2-hour low-temperature pre-aging at 70°C, allowed solute atoms in the alloy to form stable GP regions in advance, maintaining good bending formability. In Comparative Example 5, the mass percentage content of aluminum alloy raw materials is different. The lower Zn and Mg content leads to insufficient age hardening effect and the inability to form a sufficient number of η′ strengthening phases, resulting in performance inferior to Example 1. In Comparative Example 6, an Al-7Sr-1La master alloy (i.e., the mass ratio of Sr to La is 7:1) is used, with Sr:La=7:1, which is much higher than the (5~10):(8~12) specified in this invention. Excessive Sr may lead to excessive melt purification, which may introduce impurities or form brittle phases. At the same time, insufficient Re content will prevent the formation of a sufficient number of Al-Re heterogeneous nucleation cores, thus weakening the grain refinement effect. This indicates that the addition of specific proportions of components in this application has a synergistic effect, resulting in a better synergistic modification effect.

[0046] in addition, Figure 1 This is a homogeneous SEM image of the aluminum alloy casting rod of Embodiment 1 of the present invention; Figure 2 This is a homogeneous SEM image of the aluminum alloy casting rod of Embodiment 2 of the present invention; Figure 3 This is a homogeneous SEM image of the aluminum alloy casting rod from Embodiment 3 of the present invention; from Figures 1-3 As can be seen from the microstructure of the aluminum alloy cast rods prepared in Examples 1-3, the coarse non-equilibrium eutectic phase distributed along the grain boundaries in the original as-cast state has been basically dissolved. The grain boundaries have become clear and clean, with only a very small amount of fine residual phase particles remaining at a few grain boundaries. At the same time, the compositional segregation between dendrite arms has been significantly eliminated, and the microstructure is well homogeneous throughout the entire field of view, with no obvious dendrite networks or enriched regions observed.

[0047] Figure 4 This is a schematic diagram of the grain structure of the aluminum alloy formed in Embodiment 1 of the present invention; Figure 5 This is a schematic diagram of the grain structure of the aluminum alloy formed in Embodiment 2 of the present invention; Figure 6 This is a schematic diagram of the grain structure of the aluminum alloy formed in Embodiment 3 of the present invention; from Figures 4-6 As can be seen, the profile grain structure is mainly composed of fully recrystallized equiaxed grains, without obvious elongated deformed grains or fibrous structures. No obvious elongated deformed grains or fibrous structures along the extrusion direction were observed. The grain size is relatively small, and the equiaxed grain structure avoids the anisotropy caused by fibrous structures. Fine grain strengthening improves strength, while sufficient grain boundary area and uniform deformation capacity ensure plasticity.

[0048] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0049] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A method for preparing an aluminum alloy for an ultra-high strength and high toughness 7-series anti-collision beam, characterized in that, The preparation method includes the following steps: S1. Add aluminum alloy raw materials to a melting furnace for melting to obtain molten aluminum; S2. Add Al-Sr-Re rare earth modifier to the aluminum liquid, and then cast the modified aluminum liquid in a vacuum direct cooling casting system. The casting process adopts vacuum online degassing to obtain aluminum alloy casting rods. S3. The aluminum alloy casting rod is subjected to a two-stage homogenization treatment. The first stage is held at 430~450℃ for 4~6 h, and the second stage is held at 470~490℃ for 23~25 h. After treatment, it is cooled to room temperature by water. S4. Heat the homogenized casting rod to 470~500℃, with a temperature gradient of 10~30℃ between the head and tail of the casting rod; heat the extrusion die to 470~490℃ and the die cylinder to 400~410℃. S5. The preheated casting rod is extruded, and a traction machine is used to synchronously pull the material during the discharge process to obtain the extruded product. S6. The extruded product is subjected to online solution treatment, and the online solution treatment adopts an online water cooling method; S7. The product that has completed online solution treatment is subjected to straightening and cutting sawing, low temperature pre-aging treatment, bending treatment and two-stage aging treatment to obtain aluminum alloy for ultra-high strength and high toughness 7-series anti-collision beams.

2. The preparation method according to claim 1, characterized in that, The aluminum alloy raw material comprises the following chemical composition by mass percentage: Zn: 6.8~8.5%, Mg: 1.9~2.7%, Cu: 0.8~1.6%, Ti+Zr≤0.25%, Si<0.4%, Fe≤0.5%, Mn≤0.5%, Cr≤0.3%, with the balance being aluminum and unavoidable impurities.

3. The preparation method according to claim 1, characterized in that, In step S2, the casting speed is 70~80 mm / min, the flow rate of argon gas used for online degassing is 60~90 nl / min, and the rotor speed of the degassing box is 700 RPM.

4. The preparation method according to claim 1, characterized in that, In step S2, in the Al-Sr-Re rare earth modifier, Re is selected from one or more of La, Ce, Pr, and Nd, and the mass ratio of Sr to Re is (5~10):(8~12); The addition amount of the Al-Sr-Re rare earth modifier is 2.0~3.0Kg / T aluminum liquid.

5. The preparation method according to claim 1, characterized in that, In step S5, the extrusion ratio of the extrusion process is 25, and the extrusion discharge speed is 2~3m / min.

6. The preparation method according to claim 1, characterized in that, In step S6, the conductivity of the circulating water in the online water-cooling method is ≤300 μS / cm. 3 Water temperature ≤38℃, water pressure 0.4~0.5MPa.

7. The preparation method according to claim 1, characterized in that, In step S7, the straightening rate is 0.8~1.2%.

8. The preparation method according to claim 1, characterized in that, In step S7, the temperature of the low-temperature pre-aging treatment is 60~80℃, and the time is 1~3h.

9. The preparation method according to claim 1, characterized in that, In step S7, the two-stage aging treatment is as follows: the first stage of aging is carried out at 80~100℃ for 4~6 hours, and the second stage of aging is carried out at 120~140℃ for 12~16 hours.

10. An aluminum alloy for ultra-high strength and high toughness 7-series anti-collision beams, characterized in that, The aluminum alloy used in the ultra-high strength and high toughness 7-series anti-collision beam is prepared by the preparation method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • 7-series high-strength and high-bending-resistance anti-collision cross beam for automobile and manufacturing method thereof

    CN115522107A

  • High-strength aluminum alloy extrusion profile for automobile anti-collision beam and preparation method of high-strength aluminum alloy extrusion profile

    CN120210612A